THE EFFECT OF SERVICE QUALITY AND COMMUNITY RELATIONSHIP ON THE SATISFACTION OF MOTOR VEHICLES TAXPAYERS AT THE OFFICE WITH SAMSAT JEMBER - Ponang Undaghi T; Suwignyo Widagdo; Muhaimin Dimyati (STIE Mandala Jember, 2021)
This study aims to determine the effect of service quality and public relations on the satisfactionof motor vehicle taxpayers in Samsat Jember. The type of research used is Explanatory Researchusing survey methods. The population in this study is the people of Jember who have motorizedvehicle taxpayers. The sampling technique used was a non-probability sampling technique,namely the Accidental Sampling approach. The sample in this study were 100 respondents. Thedata analysis method used is multiple linear regression analysis. The results of this study indicatethat the significant value of the service quality variable on the satisfaction of motorized vehicletaxpayers in Samsat Jember is 0.008 smaller than (0.05), this means that the service qualityvariable has a significant effect on community satisfaction at the Jember Samsat Joint Office.Then the significant value of the public relations variable on the satisfaction of motorized vehicletaxpayers in the Jember Samsat is 0.000 smaller than (0.05), this means that the public relationsvariable also has a significant effect on public satisfaction at the Jember Samsat Joint Office.Keywords: Service Quality, Public Relations, Satisfaction